Capital increase and rights issue : the case of BES 2012 - Ferreira, João Diogo dos Santos (2015)
This dissertation presents a case study about the seasoned equity offering of Banco Espírito Santo, SA. This event took place on April and May 2012 and with this operation the bank raised gross proceeds of up to 1.010 million Euros. The BES Group is the second largest financial institutional in Portugal. This Capital increase was approved mainly to reach the new regulatory demands that the banking sector, subject to Bank of Portugal`s supervision, were required to achieve and BES was the only bank to do it only with market resources. I will use Black & Scholes model to evaluate the options and value of the rights for the investors and make a comparison of the results achieved in this study and the ones observed in market. In addition, I will use the methodology presented by Brown and Warner to analyze the market reaction to the announcement of the capital increase. The results of this dissertation show that the market reaction was very negative to the announcement of the capital increase and the values of the rights calculated were above the market value. Nevertheless, all the initial stipulated objectives by the bank were fully achieved.